Penentuan Jalur Distribusi Telur Ayam Menggunakan Metode Savings Matrix - Ahmad, Arfandi; Dahlan, Muhammad; Pawennari, Andi; Devitriani, Devitriani; Naja, Karisma (Metode : Jurnal Teknik Industri, 2025)
Efficiency in logistics distribution is an important aspect in improving the competitiveness of the company. UD. Gudang Telur is a company engaged in the distribution of chicken eggs located in Makassar City, facing obstacles in the form of irregular distribution routes and non-optimal utilization of transport capacity. Current distribution is carried out without paying attention to the distance factor and the location of the destination in a structured manner, so that the average transportation cost reaches Rp. 8,000,000. per month. Therefore, it is necessary to evaluate the distribution path of chicken eggs so that an optimal distribution route is obtained using the Saving Matrix method, this method allows combining several consumers in one route to minimize mileage and transportation costs. Case studies were conducted on six retailers with various travel distances and transportation capacity requirements. Based on the analysis results, the savings achieved reached 48.28% for mileage, from 163 km to 84.3 km, and 58.62% for transportation costs, from Rp 1,982,855 to Rp 820,428. These results show that the Saving Matrix method is effective in designing optimal distribution routes by considering transport capacity and distance traveled, as well as reducing significant operational costs.